2016
DOI: 10.1128/aac.00124-16
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecies Transfer of the Chromosomal Acinetobacter baumannii bla NDM-1 Carbapenemase Gene

Abstract: The species Acinetobacter baumannii is one of the most important multidrug-resistant human pathogens. To determine its virulence and antibiotic resistance determinants, the genome of the nosocomial bla NDM-1 -positive A. baumannii strain R2090 originating from Egypt was completely sequenced. Genome analysis revealed that strain R2090 is highly related to the communityacquired Australian A. baumannii strain D1279779. The two strains belong to sequence type 267 (ST267). Isolate R2090 harbored the chromosomally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 57 publications
3
56
0
Order By: Relevance
“…In line with this analogy, it is possible that blaOXA347 could be transmitted via transposons to the more virulent and invasive C. canimorsus , although no such multidrug resistant C. canimorsus have been described. Notably, this mechanism of transmission was recently shown for the chromosomally encoded blaNDM-1 carbapenemase gene in Acinetobacter baumanii [14] and OXA48 carbapenemase in highly virulent E. coli [2]. …”
Section: Discussionmentioning
confidence: 91%
“…In line with this analogy, it is possible that blaOXA347 could be transmitted via transposons to the more virulent and invasive C. canimorsus , although no such multidrug resistant C. canimorsus have been described. Notably, this mechanism of transmission was recently shown for the chromosomally encoded blaNDM-1 carbapenemase gene in Acinetobacter baumanii [14] and OXA48 carbapenemase in highly virulent E. coli [2]. …”
Section: Discussionmentioning
confidence: 91%
“…In addition to conjugation, which is the major mode of horizontal transfer of bla NDM in the Enterobacteriaceae, it has been found that OMVs of A. baumannii are able to mediate the intra-and interspecies transfer of bla NDM plasmids at high transformation frequencies (10 Ϫ5 to 10 Ϫ6 transformants in the total cell count [CFU per milliliter]) (23,60). General transduction facilitated by prophages present in the chromosome can also mediate the horizontal transfer of bla NDM between A. baumannii strains (61). More studies are required on this remarkable diversity of Acinetobacter strains carrying bla NDM and its relevance to the successful emergence of NDM across Gram-negative bacteria.…”
Section: Host Species Of Ndmmentioning
confidence: 99%
“…In Acinetobacter, the bla NDM -type genes are found to be located on either the plasmid or chromosome. Among NDM-producing A. baumannii, the bla NDM gene is usually reported to be found between two copies of the ISAba125 element, forming a composite transposon named Tn125 (158)(159)(160). Identification of a truncated form of this composite transposon in Enterobacteriaceae, while reported in its entire form in A. baumannii, strongly suggests that Acinetobacter spp.…”
Section: Antibiotic Resistance Drives Outcomesmentioning
confidence: 99%
“…Transposon-mediated passage of resistance mechanisms are well described, including those for AmpC cephalosporinases, OXA carbapenemases, KPC serine carbapenemases, and NDM or VIM metallo-carbapenemases, and aminoglycosides (101,135,136,147,148,150,155,158,159,(172)(173)(174)(175)(176)(177)(178). Indeed, transposon-mediated resistance to classically described antibiotic classes, including ␤-lactams, tetracyclines, aminoglycosides, and sulfonamides, had occurred in a global lineage of A. baumannii by the late 1970s; new resistance was subsequently acquired in transposon lineages in the 1980s as new antibiotics became available (136).…”
Section: Antibiotic Resistance Drives Outcomesmentioning
confidence: 99%